Adaptación psicométrica del Módulo de Sintaxis de la Batería de Lenguaje Objetiva y Criterial (BLOC) - Inurritigui Gonzales, Sandra (2005)
The aim of the current study was to analyze the validity and reliability of the Syntax Module of the Objective and Criterial Language Inventory (BLOC). Participants were 124 children, with ages ranged from 6 to 8 years old, both male and female in two groups: 90 children without language disorders and 34 children with language disorders. Results shown that the scores of the syntax Module of BLOC were reliable. It was also concluded that this test has a construct validity, due to the fact that the item-test correlation for every scale demonstrated to be significant, the correlation matrix reported significant associations between the scales and factor analysis showed that there is one single dominant factor.